2022
DOI: 10.1155/2022/5162768
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Gamma Globulin Combined with Azithromycin Sequential Therapy in the Treatment of RMPP and Its Effect on Th1/Th2 Cytokine Levels

Abstract: Objective. To investigate the efficacy of gamma globulin combined with azithromycin sequential therapy in the treatment of children with refractory mycoplasma pneumonia and its effect on Th1/Th2 cytokine levels. Method. From January 2021 to January 2022, 100 children diagnosed with refractory mycoplasma pneumonia were randomly divided into 2 groups (50 cases in each one), the control group was treated with azithromycin plus comprehensive basic treatment, and the treatment group was treated with combined treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%